Rare autosomal dominant mutations in GNAL are associated with primary torsion dystonia. (17th June 2013) - Kaur, A
Abstract : Mutations in GNAL cause primary torsion dystonia Fuchs et al. (2013) Nature Genetics 45: 88–92.